A relação entre os determinantes sociais em saúde e os investimentos setoriais e a mortalidade infantil em municípios brasileiros com mais de 80 mil habitantes - Mata, Matheus de Sousa (2012)
Investments in health have controversial influence on results of the health of populations, besides being subject rarely explored in literature. Moreover, from the 1970s, the social determinants of health have been consolidated in the disease process as multifactorial factors (social, economic, cultural, etc.) that directly or indirectly influence the occurrence of health problems of populations, as well as mortality rates. This study aimed to evaluate the influence of these investments and the social determinants of health on infant mortality and its neonatal and post-neonatal mortality. This is an ecological study, in which the sample was composed of Brazilians cities with over 80,000 inhabitants, avoiding fluctuations in mortality rates for common small populations, and ensure greater coverage of information systems on mortality and births Brazilians and, therefore, increase data consistency. To isolate the effect of investments in health, we used multiple linear regression. The socioeconomic indicators (p <0.001, p = 0.004, p <0.001), the inequality index (p <0.001, p = 0.001, p = 0.006) and coverage of prenatal visits (p <0.001, p <0.001; p = 0.005) were associated with infant mortality rate total, neonatal and post-neonatal, and the Gross Domestic Product per capita only influenced the overall infant mortality rate and neonatal (p=0.022; 0.045). Investments in health, in this model, lost statistical significance, showing no correlation with mortality rates among children under one year. We conclude that the social determinants of health has an influence on the variation in mortality rates of Brazilian cities, however the same was not observed for indicators of health investment